AYURVEDIC PHARMACEUTICAL DOSAGE FORMS-A REVIEW - Panda Purnendu; Das Banamali; G.C.Bhuyan; S.K.Meher; M.M.Rao (International Journal of Applied Ayurved Research, 2018)
A wide range of pharmaceutical description is available in Charaka Samhita .The basic processing techniques which known as Panchavidha Kasaya kalpana are elaborately explained in this text. Drugs are used either as single medicine or as combination in various diseases considering the prakriti of the patient, condition of the disease. For this they are converted into different forms. This process of modification can be termed as kalpana and altered form of the dravya is called kalpa.Since the panchavidha kasaya kalpana are having potency for short period, unpleasant taste etc different derived preparation (different dosage form) are evaluate by different Acharya in different time according to need.Later on these new dosage forms are known as Upkalpana. All the difficulties which arise in basic Kalpana during their preparation are overcome by these new dosage forms like easy administration, pleasant taste, safe use, high therapeutic efficacy, economic and longer shelf life period. In Ayurveda Sarangadhara Samhita is consider as an authentic book for Ayurvedic pharmaceutic because it contain clear definition of pharmaceutical term and also explained method of preparation of different formulations in simple method .Derived preparation (different dosage form) are like Churna, Vati, ghruta & Taila, Avaleha, Asava & Arista, Bhasma etc are mentioned for different disease condition in different text.